SYNTHESIS OF COPPER OXIDE NANO PARTICLES BY USING Phormidium cyanobacterium - Abdul Rahman; Amri Ismail; Desi Jumbianti; Stella Magdalena; Hanggara Sudrajat (Indonesian Journal of Chemistry, 2009)
In this paper, we report a suitable method for extracellular synthesis of copper oxide nano particles by using Phormidium cyanobacterium. We hypothesize that synthesis of copper oxide nano particles is believed to occur by extracellular hydrolysis of the cationic copper by certain metal chelating anionic proteins/reductase secreted by bacteria under simple experimental conditions like aerobic environment, neutral pH and room temperature. Proteins not only reduce Cu (II) into copper oxide nano particles (CONPs) but also plays significant role in stabilization of formed nanoparticles at room temperature. Further TEM, SEM, XRD and FTIR analysis have confirmed the synthesis of nano particles through microbial route. Extracellular induction of metal chelating proteins/reductase was analyzed by SDS-PAGE.